Mengoptimalkan Bisnis Homestay melalui Pengelolaan Keuangan yang Inklusif—Lingkup POKDARWIS Desa Pela - Ulfah, Yana; Rahmawati, Rahmawati; Arifin, Zainal; Darma, Dio Caisar (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
So far, the Tourism Awareness Group (POKDARWIS) in Pela Village has not implemented residential bookkeeping or financial management, so it often experiences problems in identifying tourism economic performance, especially income from homestays. In this context, financial management training is needed to optimize the performance of the homestay business. In this service, socialization approach, discussion and field practice methods are distributed to POKDARWIS of Pela Village. Empowerment focuses on building knowledge and skills in managing homestay finances. POKDARWIS of Pela Village was given an understanding of simple bookkeeping guidelines and direct assistance. Overall, they received the training well to support the sustainability of the homestay business through better quality financial management. It is hoped that the implications of this service will encourage POKDARWIS to apply simple financial management to the homestay business.